Ländliche siedlungsstrukturen im römischen Spanien : das Becken von Vera und das Camp de Tarragona - zwei Mikroregionen im Vergleich - Schneider, Jan, (Archaeopress Roman archaeology ;, 2017)
The present study deals with the comparison of rural settlements, aiming to compare developments in various settlements of the Iberian Peninsula during the Roman era. This is to show to what extent structures in the hinterland show parallels or are different from one another and to explore the causes of these similarities and differences. Aspects of the Roman economy must be taken into account as well as the micro-regional influences of pre-Roman settlement or topographical conditions. To achieve this goal, various aspects of rural settlements such as the dating, size or status of a place and its location and environmental conditions are analyzed and related. Archaeological, geographic and statistical methods of investigation are used. These methods, along with the complete resulting data, are fully disclosed in order to allow the comparison to be extended to other regions.